Nihongi. Chronicles of Japan from the Earliest Times to A. D. 697, translated from the original Chinese and Japanese by W. G. Aston. Charles E. Tuttle Company. Rutland, Vermont and Tokyo, Japan, 1973. - M. V, M. (Estudios de Asia y África, 1976)
-